AWSC: An approach to Web service classification based on machine learning techniques - Campo, Marcelo R.
A Web service is a Web accessible software that can be published, located and invoked by using standard Web protocols. Automatically determining the category of aWeb service, from several pre-defined categories, is an important problem with many applications such as service discovery, semantic annotation and service matching. This paper describes AWSC (Automatic Web Service Classification), an automatic classifier of Web service descriptions. AWSC exploits the connections between the category of a Web service and the information commonly found in standard descriptions. In addition, AWSC bridges different styles for describing services by combining text mining and machine learning techniques. Experimental evaluations show that this combination helps our classification system at improving its precision. In addition, we report an experimental comparison of AWSC with a related work.